OVERVIEW OF CONSTRUCTION MANAGEMENT TECHNIQUES AND ECONOMICS-A REVIEW (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Observations of many times, for expanding a knowledge of research for any particular topic or while gathering information of particular research many people searches paper and many books that task has been simplified in this paper by reviewing all the latest summary of construction management techniques, which will allow researchers of all ongoing research in construction management techniques and concerned areas and very importantly economics related to it. In this last decade the overhead expenses while running the construction is one of the major issue. The labor are very expensive almost 30-40% of the total cost is been consumed by the labor. It gives simple indication of only 60-70% cost is of material cost. Another issue that must be addressed here is the labor cost remains constant irrespective of the type of material used.